Association of Body Mass Index (BMI) with Diet, Physical Activity, and Lifestyle among Undergraduate Dental Students in a Private Dental College in Bangladesh - Rafique, Taslima; Molla, Golam Morshed; Ahamed, Asma (Update Dental College Journal, 2024)
Background: Obesity can lead to severe health problems and elevate the risk of diseases such as hypertension, dyslipidemia and diabetes due to metabolic changes. Undergraduate dental students often struggle to maintain a healthy lifestyle and eating habits due to academic pressures. BMI, a standard obesity measure, is simple to calculate and assess nutritional status, helping to identify and prevent obesity-related diseases in at-risk individuals. Method: A cross-sectional study was performed among 253 students of Sapporo Dental College, a private dental college in Uttara, Dhaka, Bangladesh, to reveal the prevalence of overweight and obesity according to BMI and its association with dietary habits, physical activities, and lifestyles among them. Data was collected using a self-written, anonymous, semi-structured questionnaire using the convenient sampling technique between July 2023 and September 2023. Result: Among the 253 participants, females (n = 190, 75.10%) are more than males (n = 63, 25%). The prevalence of normal weight, underweight, overweight, and obesity among the participants was 132 (37.93%), 31 (8.91%), 56 (16.09%), and 129 (37.07%), respectively, based on BMI. 84% of obese students were taken 1 meal from outside per day (p values < 0.05). 52% obese students did not engage in any form of physical activity on a weekly basis (p value 0.03). 55.5% obese students slept for < 6 hours every night (p-value 0.04). Conclusion: Early modifications of lifestyle improve health. Annual screenings help to prevent obesity. Fitness and diet programs can reduce dental students' chronic disease risk. Study participants are future physicians. Thus, dental students should be physically active and aware of their eating and sleep habits to reduce obesity, which might influence patients' outlooks. Update Dent. Coll. j: 2024; 14(2):15-20